THE PROSPECT OF CO-MANAGEMENT IN MANAGING OPEN WATER AND ESTUARIES RESOURCES WITH SPECIAL REFERENCE TO INDONESIA: A LESSON LEARNED - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Indonesia is a maritime country, composed about 17,500 islands. It has a great endeavor of open waterresources such as river, lake, dam, pond, swamp, etc. which are spread over the country. Multi-tribes and –races are attributed to its habits, tradition, and culture of the communities lived. Given such large territory,especially Indonesia is formed of thousands island, it will be costly to set a formal enforcement andsurveillance in securing the open-access resources (like fisheries, water, etc). Fortunately, each communityhas an indigenous or traditional system to manage the resources. For example: Ikan Larangan (in WestSumatra), sasi (in Maluku), Subak (in Bali), Sedekah Laut (in Java) and so on (Susilowati, 1996; 1999).Rather than waiting a complete formal resource management (and need to be set up by the government) anddo not know when will be effectively apply, thus it will be more reasonable and timely to revive thetraditional system of resource management belongs to the respective community. In short, communityinvolvement in resource management is urgently encouraged, particularly in developing country withlimited budget like Indonesia. This paper is attempt to compile an experienced of Co-management approachto manage the open water resource done by Susilowati (1999, 2002, 2004, 2006, 2007). An institutionalanalysis (Pomeroy and William, 1994) and Pinkerton (1989) with necessary modification were applied tothe respective studies. The results indicated that there is a fairly prospect to empower the competentstakeholders (community, government, private, independent parties) to be involved in managing the openaccessresources. However, all parties need to be encouraged for a high intention in participation,commitment and somehow to create their sense of belonging to advocate the resource management. It iseasy to say but hardly to be materialized all the things for Indonesian context, except the leaders (formal andinformal) in the respective region are really committed to conserve the resource.